(untitled) (Annual of the Faculty of Philosophy in Skopje, 2022)
New conceptions of gender built on the foundations of individual perception and freedom in the choice of gender roles have achieved rapid affirmation, among other things, thanks to the public policies that have shaped the so-called political feminism. The sociological analyzes of this instant and uncritical approach in the development of the concept of “post-gender society” emphasize the need to connect it with the analyses of the existing social structures, which indicate an enormous increase in social inequalities. The text below elaborates on some sociological dilemmas about the state of the social sciences in relation to public gender policies, dilemmas regarding the position of women in the sphere of economics where discrimination is significantly present despite the outreach programs and budget lines for public policy making.